Efeitos do treinamento físico combinado de 20 semanas sobre os aspectos imunológicos, físicos e bioquímicos de pessoas vivendo com HIV/AIDS - Garcia, Alesandro (2012)
Objective: To verify the effects of combined physical training of 20 weeks on immunological, physical and biochemical aspects of people living with HIV/AIDS Design and Methods: Ten HIV+ subjects (05 men and 05 women) with lypodistrophy and/or metabolic syndrome, treated with Highly Active Antiretroviral Therapy, participated of the present study. These individuals were subjected to CTP during 04 months. Before and after CTP, the parameters related to body composition, cardiorespiratory fitness, general biochemistry profile, and oxidative stress biomarkers were determined. Results: The CTP applied in the present work it was able to improve, significantly, the follow parameters: absolute lean mass (kg; P=0.05), HDL-c (mg⁄dL; P=0.04), abdominal resistance [maximal number of repetitions per minute (P=0.01), leg press strength (kg; P=0.02), seated row strength (kg; P=0.02), and triceps curls strength (kg; P=0.03); in addition, the CTP promoted very significant improvement in relation to: relative lean mass (%; P=0.007), maximal oxygen consumption (VO2max) (ml.kg.min; P=0.005), and thiobarbituric acid reactive substances (TBARs) (µmol/l; P=0,005). As far as concerned the parameters related to immunological system, the CTP increased the number of TCD4+ lymphocyte cells (cell counting; P=0.03). Conclusion: The CTP provoked positive changes in relation to body composition, cardiorespiratory fitness, and oxidative stress; the last one was, at least in part, reestablished. Finally, we concluded that the regular physical exercise practice is a great ally in the fight against the various dysfunctions presented by people living with HIV/AIDS.